Political communication, culture, and society - Moy, Patricia; Neumann, Rico (New York ; London : Routledge, Taylor & Francis Group, 2024)
"As an installment of Routledge's BEA Electronic Media Research Series, Political Communication, Culture, and Society focuses on the expansive concept of political communication and illuminates the processes, contents, and effects related to myriad forms and vehicles of political communication. Whether involving traditional print or broadcast media, social media platforms, or face-to-face discussions, political communication today has shaped how we perceive others and understand the world around us, including our place in it, and ultimately, how we engage with others as social, cultural, and political beings. Hailing from multiple locations and drawing on a multitude of theories as well as quantitative and qualitative methodologies, the volume's contributors examine how communication intersects with politics in a broad swath of contexts, ranging from climate change to migration to the notion of political correctness. Collectively they ask and answer questions about how today's richly textured media ecology shapes our political world and how political messages can fuel - and ameliorate - the issues that deeply cleave societies around the globe. Relevant to scholars and students of journalism, media studies, and communication sciences, this volume will help interested readers better understand today's increasingly complex sociocultural world through the lens of political communication"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Communication in politics; Mass media -- Political aspects; Public opinion -- Political aspects; Populism